Adaptive predictive state-space control of a multivariable 3-tank system - Gambier, Adrián; Unbehauen, Heinz (Decision and Control, 1999 38th IEEE Conference On, 2002)
The real time results of an adaptive multivariable generalized state-space predictive controller are presented. The control algorithm consists of a state-space receding horizon tracking system, a compensator for piecewise constant random disturbances and an estimator for parameters, state and disturbances. The estimator is based on an augmented recursive identification algorithm.